If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2(x + 3) = x + -18 Reorder the terms: 3 + -2(3 + x) = x + -18 3 + (3 * -2 + x * -2) = x + -18 3 + (-6 + -2x) = x + -18 Combine like terms: 3 + -6 = -3 -3 + -2x = x + -18 Reorder the terms: -3 + -2x = -18 + x Solving -3 + -2x = -18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + -2x + -1x = -18 + x + -1x Combine like terms: -2x + -1x = -3x -3 + -3x = -18 + x + -1x Combine like terms: x + -1x = 0 -3 + -3x = -18 + 0 -3 + -3x = -18 Add '3' to each side of the equation. -3 + 3 + -3x = -18 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = -18 + 3 -3x = -18 + 3 Combine like terms: -18 + 3 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| 5+m=8 | | (3x+1)(x-4)=0 | | 6x-2x-9= | | 5x-3=18+2x | | -10x=-100 | | 18x^2+12x+2=0 | | x+y+z=2 | | x+y-4z=-3 | | g+12=5k | | 2w-5=11 | | 8x-17=71 | | 2(x+4)=7(x-3)+34 | | X+1=-x+7 | | 2x-3y-2z=5 | | 10p-3=p+15 | | v+(v-22)+(v+21)=491 | | X+2=-2x+20 | | 6u=222 | | z+5=-13-5z | | 9q=108 | | 20=-11z-2 | | 20=-1z-2 | | 10xn= | | X^2+9X^2+20=0 | | 90+x=3x+2 | | 7x-3(2x+7)=-12 | | 9x-8-5x= | | 14=9+f | | 3(x+5)=x+7 | | y=2x+26 | | 12a+5=6(2a+5) | | 21x-11=10 |